The role of zooplankton in the pelagic-benthic coupling of the Southern Ocean - Schnack-Schiel, Sigrid B.; Isla, Enrique (Scientia Marina, 2005)
[EN] Zooplankton contributes in different ways to pelagic-benthic coupling: Their faecal material is a major route of energy flow and the vertical migrations of many species as well as the production of pelagic larvae by benthic organisms represent different paths to link the two subsystems. Antarctic particle fluxes have been shown to be highly variable in size and composition within a given region and even at the same site from year to year. There are also differences throughout the water column, where particle fluxes close to the sea floor beyond the continental shelf break do not normally show seasonal variation within shallow environments. Commonly, at depths shallower than 500 m, the most evident feature is that more than 90% of the annual fluxes occur during a short period of the spring-summer. This event is masked near the seabed at greater depths due to resupension and lateral advection of particles. Faecal material of various origins is one of the main constituents of the biogenic matter flux. It usually reaches its maximum in February once the early phytoplankton bloom has developed. However, the presence of faecal pellets is ubiquitous during the months of the year when there is enough light to support primary production. At this stage more research is needed to elucidate the particular role of distinct taxa —including among others salps, krill, copepods and protozoans— in the transport of organic matter to the benthos, and their contribution to the biogeochemical cycles of carbon, nitrogen, phosphorus and silicon. Aggregation of particles is another important process controlling the development and dynamics of pelagic-benthic coupling due to its influence on the sinking velocity of particles and the enhancement of organic matter utilisation by members of the microbial loop in the upper layers of the water column. Also in shallow waters, aggregation favours the transfer of high-quality organic matter to the benthic realm. At greater depths resuspended aggregates and single particles from shallow ...